Software-Based Digital PID Control for a Single-Tank Water Level System - Quoc-Toan Nguyen; Hai-Duong Nguyen; Anh-Tuan Nguyen; Tan-Khang Nguyen; Quoc-Hung Nguyen; Phuc-Khanh Dang; Truong-Viet Nguyen; Quoc-Bao Nguyen; Xuan-Cuong Le; Van-Hai Nguyen; Huynh-The-Hung Nguyen; Bao-Trung Mai; Phong Luu Nguyen; That-Ngoc-Hai Ton; Tan-Loc Pham; Minh-Tan Nguyen (Journal of Fuzzy Systems and Control, 2026)
The single tank system is one of the fundamental systems in the field of automatic control and is a suitable choice for implementing system control using a PID controller. Nowadays, the single tank system is widely used in laboratories for conducting experiments related to PID control. Due to its low cost, easily available components, simple construction, and ease of observation, the single tank system is an appropriate model for research in automatic control systems. The primary control method applied to the single tank system is the digital PID control method, also known as discrete PID control, the PID parameters (Kp, Kd, Ki) are selected by the trial-and-error method. Therefore, this paper investigates the variation of transient responses when changing the parameters of the PID controller in order to evaluate the model during laboratory implementation. The main objective of this paper is to design a discrete PID controller through simulation and to experimentally investigate its performance on a real single tank system. Experimental results show that the system operates stably, and the pump speed can be adjusted by changing the parameters of the PID controller. The overshoot starts at over 0.2%, the steady-state error is about 0.02 cm, and the settling time is approximately 4.5 to 5 seconds.